Does Anyone Value Criticism Talk about the Pathology of Book Review Status - Seyed Mahdi Zarghani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
For a while I wanted to write a note about the state of literary criticism in our beloved country, and I must thank Mr. Emmarati Moghaddam for providing me with the opportunity to do this by writing "Review and Critique of Muslim Philosophers' Poetic Treatises using Aristotle's Poetry Technique: Translation in Times of Want". But first of all, let me say that this article is not a "response to the criticism of a young and talented scholar", rather a discussion of the "style of criticism" which has become popular in critical writing these days and seems to me to be detrimental to literary criticism; a way part of which is probably related to our generation, and as a teacher of that generation I hold myself responsible and partly to blame for that. Sometimes most critics are middle-aged, sometimes the work of critique is given to the elderly and sometimes younger critics are active. Each of these three situations has its own requirements, benefits, and drawbacks that can be addressed in turn. It seems that in the current situation there are more young, talented and aspiring critics who fortunately enter the field of criticism and theorizing one after another. This situation gives us a clear perspective on literary criticism, provided we are all careful neither to involve into "stagnation and compliment and complacency" nor to fall into the trap of "being uncritical." In the other hand, unlike the masters of the generation before us who often adopting a "strategy of silence" against the criticism of their work, found themselves practically as superior than critics or to be criticized, I think the time of so sacred self-concept and knowing ourselves superior to criticism is over, and by responding to criticism from critics, we can accomplish our task of advancing the process of criticism and possibly directing it. Our response to the criticisms written on our works is, first and foremost, the respect for criticism and, second, for the personality of critic, both of which are useful and have good results. I will try to address some of the objections raised in Mr. Emmarati Moghaddam's article, while criticizing the state of literary criticism in our country.